The Protective Effect of Evodiamine in Osteoarthritis: An In Vitro and In Vivo Study in Mice Model - Xian, Shuyuan; Lin, Zeng; Zhou, Chao; Wu, Xing (Frontiers in Pharmacology, 2022)
Osteoarthritis (OA) is a chronic and costly disease characterized by cartilage degradation and joint inflammation. Evodiamine (EV), which can be extracted from Evodia rutaecarpa (Rutaceae), is a traditional Chinese medicine to treat inflammation, cardiovascular disorders, infection, and obesity. Studies have shown that EV can suppress the activation of immune cells and restrain the secretion of pro-inflammatory cytokines. However, it is still not well known about its role in the treatment of OA. In this study, we utilized interleukin-1β (IL-1β) stimulated mouse chondrocytes in vitro and the destabilization of the medial meniscus (DMM) model in vivo to demonstrate the anti-inflammatory properties of EV in OA. The results suggested that EV decreased the generation of NO, IL-6, TNF-α, and PGE2. Meanwhile, the increased expression of INOS, COX-2, MMP-13, and the degradation of Aggrecan and Col-II, were significantly alleviated by EV in IL-1β-activated mouse chondrocytes. Moreover, EV can inhibit the considerable IL-1β-stimulated phosphorylation of the NF-kB signaling pathway and nuclear translocation of p65. compared with the control group. Furthermore, EV alleviated the cartilage degeneration and reversed the increased Osteoarthritis Research Society International (OARSI) scores in the OA model in vivo. Our study demonstrates that EV can suppress the inflammation in vitro and the cartilage degeneration in vivo in OA, which implies that EV maybe be a potential candidate for the treatment of OA.